UN MONDO DENTRO IL MONDO. ALEXANDR SOKUROV E I MUSEI: ARCA RUSA E FRANCOFONIA - Roberto CHIESI, (Fonseca, Journal of Communication, 2023)
In Aleksandr Sokurov’s films, Russian Ark (Russkiy kovcheg, 2002) and Francofonia (id.,2015), the museums, the Hermitage in St. Petersburg and the Louvre in Paris, become protagonists. The mazy space of the museum, as a place where the great works of art in the world are preserved, is a temple of memory and past. But this wealth of knowledge is not seen by Sokurov exclusively as a treasure of artistic and historical culture and erudition, but also as a theater of the collective imagination of a country.